The parental role in the support structure of grade eleven students at Sitintile Secondary School - Jele, Bhekumuzi Sipho Kenneth (2012)
M.Ed. === The purpose of this study is to investigate the parental involvement in the education of their children. This research study is also an endeavour to explore the views of parents of students in grade eleven at Sitintile secondary school and on their role as support structure. In gathering data, qualitative research methods were used. This qualitative research methods lead to the understanding of people's perceptions. Processes that were involved in the data collection were one to one interviews with each of the twelve parents and observation was employed as the secondary data collection method. The researcher approached twelve individuals and they were identified as the sample population of the study . . The main implications of these findings could be summed up this way: • For the grade eleven students to prosper and be goal directed, parent-teacher relationship need to be enhanced. • There is a need for the parents to involve parents in the education of their children. • In conclusion, parents must play a meaningful role in the education of children.